The Road: o tema da violência da escrita para as telas - Nunes, Francisco Romário (2015)
This paper analyzes the translation of the book The Road (2006), by Cormac McCarthy, to cinema, focusing on the theme of violence and the way it was translated to film. The Road tells the story of a father and his son; both are survivors of a disaster on Earth. They walk towards the south coast of the United States. During this journey, the characters remake the American History, a country that obtained its territorial expansion from north to south. Nevertheless, there is nothing to be conquered because the West lives post-apocalyptic days. On this regard, the characters wander among corpses seeking protection from the groups that practice cannibalism. Having this plot, the novel achieved popularity in its home country, as well as it obtained academic prestige, which culminated with the Pulitzer Prize for fiction. Three years after its release, The Road was adapted to a film with the same tittle, directed by John Hillcoat. Our main aim, then, is to investigate which strategies the director used to translate the theme of violence in cinema. We assume that the film translated violence according to the patterns of Hollywood melodrama, through a narrative construction that intends to make the spectator have affection for the characters. For this purpose, we based our research on some authors of Translation Studies: Lefevere (1992), Toury (1995) and Even-Zohar (1990). Thereafter, we studied some theories concerning adaptation from literature to screen according to Cattrysse (1992), Stam (2008) and Hutcheon (2013). Related to cinema theory, we studied Machado (2011), Xavier (2003, 2012) and Bordwell (1985). We also investigated the depiction of violence in literature and in the film, according to the authors Leenhardt (1990), Lins (1990), Ginzburg (2012), Abel (2007), Hikiji (2012) and Mongin (1999). Finally, we discussed some critical essays on McCarthy, pointing out Cant (2009), Ellis (2006), Walsh (2009), and Hage (2010), among others. The results showed that the adaptation translated violence in a way it reinforced the melodrama, highlighting the characters’ hazardous condition in both the time and the space of this narrative film, and incorporating narrative strategies which could make the spectator identify with the father and his son.